EFEKTIVITAS SEDIAAN SERUM WAJAH EKSTRAK RAMBUT JAGUNG (Zea mays L.) TERHADAP Propionibacterium acne - ramadani, ananda; Siti Nurhalisa; Andi Amalia Khairul Putri (Akademi Farmasi Yamasi Makassar, 2024)
This study aims to determine the effectiveness of facial serum preparations of corn hair extract (Zea mays L.) on the growth of Propionibacterium acnes. The research method used was experimental laboratory research, to determine the effectiveness of corn silk extract serum (Zea mays L.) against Propionibacterium acnes which was carried out at the Microbiology Laboratory of the Yamasi Pharmacy Academy, Makassar. Corn silk (Zea mays L.) was extracted using the maceration method using 96% ethanol solvent, the extract obtained was then made into a serum preparation with a concentration of (F1) 6% w/w, (F2) 8% w/w, (F3) 10% w/w and (F4) as serum base. The results of the study stated that corn hair extract (Zea mays L.) with a concentration of 10% was more effective in inhibiting the growth of Propionibacterium acnes Abdiana, R. (2017 ). Rambut Jagung (Zea mays L.) Sebagai alternatif Tabir Surya Corn Silk As An Alternatif to sunscreen. Indonesia journal of pharmaceutical Science and Technology, 31-35. Alfianti, A. A. (2020). Aktivitas Sediaan Gel Handsanitizer Ekstrak Etanol Limbah Rambut Jagung (Zea Mays L.) Terhadap Staphylococcus Aureus. Univeristas Muslim Nusantara Al-Washliyah. Fajrina, A., Dinni, D., Bakhtra, A., Eriadi, A., Chania Putri, W., & Wahyuni, S. (2021). Uji Aktivitas Antibakteri Ekstrak Etanol Rambut Jagung (Zea maysL.) Terhadap Bakteri Streptococcus mutansdan Porphyromonas gingivalis. Jurnal Farmasi Higea, 13(2). Harunnisa, Kartikasari, D., Rahman, I. R., & Kurnianti, E. (2022). Formulasi Sediaan Serum Ekstrak Etanol Kulit Buah Tampoi (Baccaurea macrocarpa) Sebagai Antioksidan Dengan Variasi Konsentrasi Ekstrak. Ilmiah Pharmacy, 9(2), 11–23. Hasrawati, A., Hardianti, H., Qama, A., & Wais, M. (2020). Pengembangan Ekstrak Etanol Limbah Biji Pepaya (Carica papaya L.) Sebagai Serum Antijerawat. Jurnal Fitofarmaka Indonesia, 7(1), 1–8. https://doi.org/10.33096/jffi.v7i1.458. Ismiati, E. R. (2015). Aktivitas Antioksidan Minuman Herbal Rambut Jagung dengan Variasi Kondisi dan Lama Perebusan. Universitas Muhammadiyah Surakarta. kusriani, H. M. (2017 ). aktivitas antioksidan dan tabir surya dari tongkol dan rambut jagung (Zea mays L.) . sekolah tinggi farmasi bandung vol 4. nurbaity.(2020). Efektivitas Ekstrak Etanol Daun Arika (Vernonia amigdalina Del.) Terhadap Bakteri Staphylococcus aureus. Universitas Muhammadiyah Magelang , 6-9. Yanti, N. R. (2020). Aktivitas Sediaan Gel Anti Acne Ekstrak Etanol Limbah Rambut Jagung (Zea Mays L.) Terhadap Propionibacterium Acnes. Universitas Muslim Nusantara Al-Washliyah